From Quiet to Noisy Politics: Transformations of Swiss Business Elites' Power*. (March 2021) - Mach, André; David, Thomas; Ginalski, Stéphanie; Bühlmann, Felix
During most of the twentieth century, it was possible to consider Switzerland a coordinated market economy, characterized by dense interfirm networks and the strong role of business associations. Thanks to their cohesion and collective organization, in a context of quiet politics and informal institutions, business elites could largely self-regulate major socioeconomic issues in the shadow of politics. However, since the end of the twentieth century, Swiss business elites have undergone profound changes not only in their composition, but also in their coordinating capacity, their growing political divisions, and their connections to politics. This growing sociological and political fragmentation, combined with changes in the way of doing politics, through noisier and more formal politics, has weakened the instrumental power of Swiss business elites. To compensate for this loss of direct influence, business elites of the largest Swiss companies have developed new political strategies, relying on their growing structural power in a context of global and financial capitalism.